Microbiome, Immunosenescence, and Chronic Kidney Disease - Stavropoulou, Elisavet; Kantartzi, Konstantia; Tsigalou, Christina; Aftzoglou, Konstantina; Voidarou, Chrysa; Konstantinidis, Theocharis; Chifiriuc, Mariana Carmen; Thodis, Elias; Bezirtzoglou, Eugenia (Frontiers in Medicine, 2021)
The gut microbiome is known as an important predictive tool for perceiving characteristic shifts in disease states. Multiple renal diseases and pathologies seem to be associated with gut dysbiosis which directly affects host homeostasis. The gastrointestinal-kidney dialogue confers interesting information about the pathogenesis of multiple kidney diseases. Moreover, aging is followed by specific shifts in the human microbiome, and gradual elimination of physiological functions predisposes the microbiome to inflammaging, sarcopenia, and disease. Aging is characterized by a microbiota with an abundance of disease-associated pathobionts. Multiple factors such as the immune system, environment, medication, diet, and genetic endowment are involved in determining the age of the microbiome in health and disease. Our present review promotes recently acquired knowledge and is expected to inspire researchers to advance studies and investigations on the involved pathways of the gut microbiota and kidney axis.